Hypointense signals in the infrapatellar fat pad assessed by magnetic resonance imaging are associated with knee symptoms and structure in older adults: a cohort study. Issue 1 (December 2016) - Han, Weiyu; Aitken, Dawn; Zhu, Zhaohua; Halliday, Andrew; Wang, Xia; Antony, Benny; Cicuttini, Flavia; Jones, Graeme; Ding, Changhai
Abstract Background There are few clinical and epidemiological studies reporting the association between abnormal changes within the IPFP and knee osteoarthritic changes. This study aims to describe the associations between hypointense signals in the infrapatellar fat pad (IPFP) and knee structural change and symptoms in older adults. Methods Participants (n = 874) were selected randomly from local community and followed up 2.7 years later (range 2.6–3.3 years). T1- or T2-weighted fat-suppressed magnetic resonance imaging (MRI) was assessed for IPFP hypointense signal, cartilage volume, cartilage defects, and bone marrow lesions (BMLs). Knee pain was assessed by self-administered Western Ontario and McMaster Osteoarthritis Index (WOMAC) questionnaire. Radiographic osteoarthritis was assessed using the OARSI atlas. Results Cross-sectionally, hypointense signals in the IPFP were significantly associated with a higher risk of knee cartilage defects at all sites, tibiofemoral BMLs and knee pain in multivariable analyses. Longitudinally, baseline signal abnormalities were significantly and positively associated with increases in knee cartilage defects (OR: 2.27, 95 % CI: 1.61–3.21), BMLs (OR: 1.91, 95 % CI: 1.39–2.62), and knee pain (OR: 1.36, 95 % CI: 1.05–1.76) in multivariable analyses. The associations with cartilage defects remained significant after adjustment for BMLs, but the associations with BMLs and knee pain decreased in magnitude or became non-significant after further adjustment for cartilage defects. Conclusions Hypointense signals in the IPFP were associated primarily with increased knee cartilage defects and also with BMLs and knee symptoms in cross-sectional and longitudinal analyses, suggesting the abnormality represented by this signal has a potentially important role in osteoarthritis progression.